Availability Payments and Key Performance Indicators: Challenges for Effective Implementation of Performance Management Systems in Transportation Public-Private Partnerships. (July 2014) - Lawther, Wendell C.; Martin, Lawrence
Recent economic problems have led to a potential increase in the adoption of an availability payments approach by U.S. transportation agencies when creating public-private partnerships (P3s). In doing so, the public sector assumes 100% of the demand risk, relying much more heavily on performance management systems that contain key performance indicators (KPIs) to ensure optimal private partner performance during operations and maintenance. Many existing performance management systems, however, suffer from a lack of alignment among KPIs chosen to ensure that all P3s meet societal or agency goals as well as project goals. Furthermore, the choice of KPIs and accompanying standards has resulted in standards that are too easily met or inappropriately weighed. Examples are provided from P3 contracts for projects in Australia and Canada.